PENGARUH PENDAYAGUNAAN ZAKAT PRODUKTIF TERHADAP KESEJAHTERAAN MUSTAHIK PADA PROGRAM UNIT USAHA EKONOMI KELUARGA - Ghifar, Muhammad Dzil; Prestianawati, Silvi Asna (Islamic Economics and finance in Focus, 2023)
Zakat has the potential to be an effective means of empowering the people's economy. Seeing from the majority of Indonesia's population, the majority adheres to Islam. The large number of Indonesians who embrace Islam is 87.2% or around 207,176,162 people of all religions recognized in Indonesia. The main weakness of mustahik to be able to start a small business is actually the mental attitude and readiness of business management. For this reason, giving zakat with the aim of starting a productive business at the initial stage must be accompanied by a companion who is able to educate mustahik. This study aims to analyze the role of utilization of productive zakat on the welfare of mustahik in the Family Economic Business Unit program at the Amil Zakat Infaq Shadaqah Muhammadiyah Institute. This research was conducted at Parepare in April 2023 involving 30 respondents who were selected using a non-probability sampling technique. Data analysis was performed using multiple linear regression methods. The results of this study indicate that the variable of business capital received has a significant effect on the welfare of mustahik, the variable of distribution of zakat has a significant effect on the welfare of mustahik, and the variable of utilization of zakat has a significant effect on the welfare of mustahik